1994
DOI: 10.1002/hep.1840200604
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and extrahepatic hepatitis C virus replication in relation to response to interferon therapy

Abstract: Response to a 1-yr course of interferon-alpha 2b was assessed in 18 patients with chronic hepatitis C virus infection in relation to clinical, biochemical and histological parameters and to the presence or absence of hepatitis C virus RNA and the presumed replicative form of the virus (negative-strand hepatitis C virus RNA) in serum, liver and peripheral blood mononuclear cells. The findings were compared with those in seven untreated patients studied over the same period. At the start of the study, positive-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…For example, several studies have found that HCV RNA may be present in PBMCs but not the corresponding serum or liver. [98][99][100][101] Thus, current detection systems may underestimate the true extent of replication. Moreover, HCV RNA, including replicative intermediate forms, can persist at very low levels in peripheral lymphoid cells for many years after apparently complete spontaneous or treatment-induced resolution of chronic HCV, 102 strongly suggesting that sub-populations within PBMCs may represent true reservoirs of HCV replication.…”
Section: Clinical Implications Of Extrahepatic Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several studies have found that HCV RNA may be present in PBMCs but not the corresponding serum or liver. [98][99][100][101] Thus, current detection systems may underestimate the true extent of replication. Moreover, HCV RNA, including replicative intermediate forms, can persist at very low levels in peripheral lymphoid cells for many years after apparently complete spontaneous or treatment-induced resolution of chronic HCV, 102 strongly suggesting that sub-populations within PBMCs may represent true reservoirs of HCV replication.…”
Section: Clinical Implications Of Extrahepatic Replicationmentioning
confidence: 99%
“…103 Thus, it is provocative to speculate that low-level replication of HCV in PBMCs may lead to reactivation of HCV after termination of therapy and/or predict response to therapy. 80,99,100,[102][103][104][105] As reviewed elsewhere, HCV is likely involved in several neurologic syndromes. 16 While central nervous system (CNS) involvement is less frequent, the detection of negative-strand HCV RNA in the CNS 29 suggests a potential link between HCV and these extrahepatic pathol- ogies.…”
Section: Clinical Implications Of Extrahepatic Replicationmentioning
confidence: 99%
“…Positive-strand HCV RNA has indeed been detected by reverse-transcription polymerase chain reaction (RT-PCR) in peripheral blood mononuclear cells (PBMC) in several studies investigating patients at various stages of the viral infection. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Furthermore, it was possible in some cases to detect the negative strand of HCV RNA, and thus to suggest that HCV RNA might replicate in these cells. [11][12][13][14][15][16][17][18][19][20][21] These findings were further substantiated by the detection of HCV genomes in PBMC and liver mononuclear cells by using in situ hybridization.…”
mentioning
confidence: 99%
“…Several groups have described the detection of HCV negative strand, a viral replicative intermediate, in peripheral blood mononuclear cells (PBMCs) (Wang et al, 1992 ;Muller et al, 1993 ;Gabrielli et al, 1994 ;Saleh et al, 1994), and it has been reported that a human T-cell line is capable of supporting a productive infection (Shimizu et al, 1993). However, the strand specificity of RT-PCR, which is currently the only suitable method for the detection of HCV RNA, has recently been questioned : this assay has been demonstrated to be prone to false priming of the incorrect strand or to self-priming related to RNA secondary structures (Lanford et al, 1994).…”
mentioning
confidence: 99%